2013
DOI: 10.1128/aac.00709-13
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive Streptomycin Resistance Mutations Decrease the Formation of Attaching and Effacing Lesions in Escherichia coli O157:H7 Strains

Abstract: dStreptomycin binds to the bacterial ribosome and disrupts protein synthesis by promoting misreading of mRNA. Restrictive mutations on the ribosomal subunit protein S12 confer a streptomycin resistance (Str r ) phenotype and concomitantly increase the accuracy of the decoding process and decrease the rate of translation. Spontaneous Str r mutants of Escherichia coli O157:H7 have been generated for in vivo studies to promote colonization and to provide a selective marker for this pathogen. The locus of enterocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Therefore, streptomycin treatment is commonly used to suppress facultative anaerobes to allow E . coli to overcome colonization resistance in mice ( Chen et al, 2013 ; Leatham et al, 2009 ; Mohawk and O'Brien, 2011 ). The exact mechanism of reduction of colonization resistance after streptomycin administration is unclear, but elimination of microbe-microbe interactions and a streptomycin-induced inflammatory response to support growth of E .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, streptomycin treatment is commonly used to suppress facultative anaerobes to allow E . coli to overcome colonization resistance in mice ( Chen et al, 2013 ; Leatham et al, 2009 ; Mohawk and O'Brien, 2011 ). The exact mechanism of reduction of colonization resistance after streptomycin administration is unclear, but elimination of microbe-microbe interactions and a streptomycin-induced inflammatory response to support growth of E .…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of using spontaneous streptomycin-resistant E . coli strains is that they may have slight to significant decreases in colonization factor expression that could influence host-pathogen interactions ( Chen et al, 2013 ). In addition, streptomycin treatment alone leads to a modest increase in histopathological changes, making the intestine more irritable ( Spees et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two common rpsL mutations in E. coli that confer STR R are the replacement of the amino acid lysine 42 with threonine (referred to as K42T) and the replacement of the amino acid lysine 87 with arginine (referred to as K87R) . While the K42T mutation also results in error‐restrictive ribosomes , the K87R mutation results in semi error‐restrictive ribosomes, with a translational error rate that is lower than that of wild‐type strain yet higher than error‐restrictive strains such as the K42T mutant . On the other hand, it was demonstrated that a single amino acid substitution in the E. coli rpsE gene of a highly conserved glycine to an aspartate at position 28 (referred to G28D), which produces SPEC R , also resulted in error‐prone ribosomes .…”
Section: Introductionmentioning
confidence: 99%
“…This is because chromosomal resistance mutations frequently occur as molecular changes in the targets of antibiotics, and these targets are generally highly conserved structures that are central to bacterial metabolism, for example, the ribosomes and nucleic acid polymerases ( Munita and Arias 2016 ). Changes in these target sites often come at a high cost by reducing bacterial growth rate ( Chen et al. 2013 ; Cohan, King, and Zawadzki 1994 ; Gagneux et al.…”
mentioning
confidence: 99%